Being and dwelling through tourism an anthropological perspective - Palmer, Catherine (New directions in tourism analysis, 2018)
"Much of the literature about tourism seeks to make sense of tourism on the basis of singular approaches such as visuality, identity, mobilities, myth making, tourism as a type of performance or as a form of globalised consumption. However, as insightful and valuable as these approaches are, what is missing is an overarching framework within which they can be located. This book offers one such framework by drawing upon the insights that can be gained from social anthropology. In doing so the book provides a response to ongoing debates seeking new ways to redefine and re-theorise the phenomenon of tourism. Taking her theoretical approach from Heidegger's philosophical essay from the 1950's 'Building Dwelling Thinking', Catherine Palmer uses his dwelling perspective as the starting point from which to consider the following questions: - What does dwelling mean in the context of tourism? - In what ways do people dwell through tourism? - How does dwelling through tourism relate to being in the world? - How can a dwelling perspective contribute to understanding the role of tourism in making and remaking what it means to be human? This theoretically substantive book is of interest to researchers involved with tourism research from a wide range of disciplines including anthropology, sociology, geography, cultural studies, leisure studies and tourist studies"...